Evaluation of correlation between sleep quality and chronic periodontitis - A case-control study - Subash Lenin; Dorairaj Jayachandran; Sunantha Selvaraj; Bhavani Balakrishnan (Wolters Kluwer Medknow Publications, 2024)
Background Periodontitis poses a significant public health challenge globally due to its substantial contribution to tooth loss and its links to numerous systemic diseases. Sleep, being a complex biological process crucial for overall mental and physical well-being, intersects with this concern. However, recent studies have yielded conflicting findings on the potential connection between chronic periodontitis and sleep quality, likely due to the shared inflammation characteristic in both conditions. Aim The study aims to examine the correlation between the quality of sleep and chronic periodontitis. Materials and Methods This study involved 100 participants who underwent a thorough clinical periodontal examination. The sleep quality was evaluated using the Pittsburgh Sleep Quality Index. Univariate and multivariate logistic regression analyses were conducted to assess the impact of various factors in the presence of periodontitis. Statistical analysis was performed, with statistical significance at P ≤ 0.05. Results In the current study, 29% of the participants exhibited poor sleep quality, and 75.8% were in the periodontitis group. Poor sleep quality was associated with periodontitis in univariate (crude odds ratio = 1.83, 95% confidence interval = 0.655-0.847; P = 0.004) analyzed. Patients' age showed a positive correlation with periodontitis. Other variables do not show a statistically significant level. Conclusion The present study shows that there lies a significant correlation between chronic periodontitis and poor sleep quality. Among the measured covariables, only age showed a significant relationship with periodontitis.